A Cross-Cultural Analysis of the COVID-19 Pandemic's Impact on Antenatal Healthcare-Seeking Behaviors in Ghana and the United States. (November 2021) - Norris, Katharine G; Huang, Phoebe A; Glantz, J. Christopher; Kodam, Ruth-Sally; Anto-Ocrah, Martina
The coronavirus (COVID-19) pandemic impacted healthcare systems worldwide. In this study, we conducted qualitative interviews with pregnant women in Ghana and the United States (US) to understand their antenatal care (ANC) experience. Adapting to the virtual nature of the pandemic, social media platforms Facebook and WhatsApp were used to recruit, consent, enroll, and interview women. Interviewers used a semi-structured guide with content validated by the US and Ghanaian collaborators. Audio recordings of the interviews were transcribed, coded using Dedoose (v8.0.35, Dedoose) and grounded theory, and analyzed for recurring themes. Between May and July 2020, 32 women (15 Ghanaians, 17 Americans), aged 25–40 years were interviewed. Major themes emerged: (i) apprehension about ANC services; (ii) disruptions to planned healthcare provider use; and (iii) changes in social support. Although the women strove to retain their ANC as planned, the pandemic universally caused several unanticipated changes. Given associations between higher maternal mortality and poor outcomes with inadequate ANC, specific policies and resources for telehealth education and intra- and postpartum support should be implemented to reduce disruptions to ANC imposed by COVID-19.